2003
DOI: 10.13181/mji.v12i4.119
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Anopheles spp in the villages of Salubarana and Kadaila, Mamuju District, South Sulawesi Province, Indonesia

Abstract: telah diteliti selama bulan Juli sampai December 2002 untuk mendapatkan data dasar yang berkaitan dengan faktor parasit, vektor, inang, dan lingkungan. Survei malariometrik bulanan selama kurun waktu 6 bulan menemukan suatu prevalensi malaria yang relatif tinggi di Kadaila dibandingkan dengan Salubarana. Kadaila terutama dihuni oleh transmigran dari Jawa, Bali, Lombok dan dari kabupaten lain di Sulawesi Selatan, sedangkan Salubarana dihuni oleh penduduk asli suku Mandar. Pada analisis 1.113 apusan darah yang d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…A previous study showed that antibody response to MSP1 and apical membrane antigen 1(AMA-1) is higher in high transmission season in comparison to the low transmission season. The findings are in accordance with the results of this study where the antibody response to the three merozoite antigens examined was found to be higher in the wet season when the transmission was high [ 10 , 20 ]. In a cohort study in Gambian children, increased levels of serum IgG antibodies against P. falciparum merozoite antigens were observed in many children during the rainy season.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A previous study showed that antibody response to MSP1 and apical membrane antigen 1(AMA-1) is higher in high transmission season in comparison to the low transmission season. The findings are in accordance with the results of this study where the antibody response to the three merozoite antigens examined was found to be higher in the wet season when the transmission was high [ 10 , 20 ]. In a cohort study in Gambian children, increased levels of serum IgG antibodies against P. falciparum merozoite antigens were observed in many children during the rainy season.…”
Section: Discussionsupporting
confidence: 92%
“…The population mainly consists of Mandarese and Buginese ethnic groups with some resettlers from the islands of Java, Bali and Lombok. This area is known to be endemic for malaria and lymphatic filariasis [ 10 ]. Multistage, random sampling cross-sectional surveys was conducted in Mamuju District, West Sulawesi Province, Indonesia during the dry and wet seasons of 2010.…”
Section: Methodsmentioning
confidence: 99%
“…An. barbirostris has been confirmed as a vector of malaria in two villages in Mamuju, where other supporting factors are the presence of transmigrants from Java, Lombok, Bali, and other districts in South Sulawesi (Nurdin et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The second-highest number of mosquitoes in Maros and North Toraja was Anopheles. Anopheles can breed in both rivers and soil (Nurdin et al 2003), and this caused Anopheles to remain abundant in the wet season (21.25%) and the dry season (22.58%). Anopheles larvae can be found in various waterways, puddles, and ponds (Inunggita et al 2019), also found in the same place with Culex larvae (Nchoutpouen et al 2019), thus Anopheles was also abundant in place with many Culex breeding sites, such as Maros and North Toraja.…”
Section: Resultsmentioning
confidence: 99%
“…Belum pernah dilaporkan adanya vektor JE di Kabupaten Pangkajene dan Kepulauan. 6,7 Keberadaan vektor kemungkinan berbeda menurut variasi ekosistem. Eksosistem dibagi menjadi tiga yaitu eksosistem hutan, non hutan dan pantai.…”
Section: Pendahuluanunclassified